Exploring potential key genes and disease mechanisms in early-onset genetic epilepsy via integrated bioinformatics analysis - Vasiliki Boulaki; Spiros Efthimiopoulos; Nicholas K. Moschonas; George Μ. Spyrou (Neurobiology of Disease)
Epilepsy is a severe common neurological disease affecting all ages. Epilepsy with onset before the age of 5 years, designated early-onset epilepsy (EOE), is of special importance. According to previous studies, genetic factors contribute significantly to the pathogenesis of EOE that remains unclear and must be explored. So, a list of 229 well-selected EOE-associated genes expressed in the brain was created for the investigation of genetic factors and molecular mechanisms involved in its pathogenesis. Enrichment analysis showed that among significant pathways were nicotine addiction, GABAergic synapse, synaptic vesicle cycle, regulation of membrane potential, cholinergic synapse, dopaminergic synapse, and morphine addiction. Performing an integrated analysis as well as protein-protein interaction network-based approaches with the use of GO, KEGG, ClueGO, cytoHubba and 3 network metrics, 12 hub genes were identified, seven of which, CDKL5, GABRA1, KCNQ2, KCNQ3, SCN1A, SCN8A and STXBP1, were identified as key genes (via Venn diagram analysis). These key genes are mostly enriched in SNARE interactions in vesicular transport, regulation of membrane potential and synaptic vesicle exocytosis. Clustering analysis of the PPI network via MCODE showed significant functional modules, indicating also other pathways such as N-Glycan biosynthesis and protein N-linked glycosylation, retrograde endocannabinoid signaling, mTOR signaling and aminoacyl-tRNA biosynthesis. Drug-gene interaction analysis identified a number of drugs as potential medications for EOE, among which the non-FDA approved drugs azetukalner (under clinical development), indiplon and ICA-105665 and the FDA approved drugs retigabine, ganaxolone and methohexital.